Seepage-zone recognition of river water based on Cl(-) spatial difference - Ji, Hongying (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
Based on Cl(-) monitoring data of river water and shallow groundwater samples on both sides of the Dashi River, we analyzed spatial distribution of Cl(-) content in surface water and groundwater, and evaluated the retardation strength, pCl(-), the average retardation strength, pA, and the average residual retardation strength, pAR, of surface-groundwater Cl(-) content. We introduce the difference, Q, of the average retardation strength and the average residual retardation strength, which can be used to identify the seepage zone and the transition seepage zone of the river, and to quantitatively express the seepage range. The results show that Cl(-) content in the river gradually increased in areas with industrial agglomeration, but decreased in areas with non-agglomeration, and gradually decreased along the river flow. If Q ≥ 0, then there is no seepage zone in the study area, but if Q < 0, then there is a seepage zone in the study area. The sampling point is in the seepage zone when pCl(-) ≤ pA, in the transition seepage zone when pA < pCl(-) ≤ pAR, and in the no-seepage zone when pCl(-) > pAR. The recognition results are more consistent with field investigation